Retailing management - Levy, Michael; Weitz, Barton A. (New York Mcgraw-Hill College, 2000)
Retailing has become a high-tech, global industry. Retailing Management covers the latest developments in information technology for retailers. It also covers current trends and practices in international retailing. An interactive website offers additional resources for the reader.
Keywords: Management -- Retaling Management